Does sounding ‘Gay’ or ‘Straight’ affect how we understand language? Sentence comprehension is regulated by the speaker's perceived sexual orientation - Sulpizio, S.; Fasoli, F.; Lapomarda, G.; Vespignani, F. (Journal of Neurolinguistics, 2025)
Social interactions are shaped by the way individuals communicate. Listeners form impressions based on how someone sounds, and the message conveyed can be interpreted differently depending on who the speaker is. We investigated on-line sentence processing focusing on the role of the speaker's gay- vs. heterosexual-sounding voice in the construction of meaning. Event-related brain potentials were recorded while participants listened to two gay- and two heterosexual-sounding male speakers uttering stereotypical sentences. We manipulated whether the sentences referred to professions stereotypically congruent or incongruent with the speakers' perceived sexual orientation. Results showed that the interplay between the speaker's voice and message content influenced sentence processing early after an incongruent stereotype was presented. The interaction was maximal at frontal sites, with a larger negativity for stereotypically-congruent than for stereotypically-incongruent professions when uttered by gay-sounding speakers. These results suggest that the perception of the speaker as gay- or straight-sounding is quickly used by listeners to build the message meaning. The inconsistency between vocal and linguistic information modulates a frontal negativity, potentially indicating control processes during sentence comprehension put in place to deal with the inconsistency.